Prospects for the development of the legal culture of the society regarding human rights (Czech Journal of Multidisciplinary Innovations, 2024)
In this article, the contents of the reforms carried out with the aim of ensuring the rights and freedoms of every member of the society are citizens and individuals. How important the role of legal culture is in this area is reflected. Attention is focused on the issues of the need to ensure human rights in a legally literate and cultured society